PENGKEMASAN KULINER LOKAL DAN CINDERAMATA LOKAL DALAM MENDUKUNG PENGEMBANGAN DESA WISATA TISTA, KECAMATAN KERAMBITAN, KABUPATEN TABANAN - Muriawan Putra, Agus; Aryanti, Ni Nyoman Sri; Astina, IB. Ketut; Setiawan, IB. Dwi (Buletin Udayana Mengabdi, 2018)
Tista village has a very diverse potential to be developed into a tourist attraction, namely the potential of nature, cultural potential, culinary potential, spiritual potential, and of course the potential of Human Resources. These potentials are the capital of Tista Village to be a tourist village, where Tista Village is designated as a tourist village by the Regent of Tabanan Number: 180/319/03 / HK & HAM / 2016, 26th October 2016. Tista villagers strongly support the village to be a rural tourism, this can be proven by the enthusiasm of the community held Tista Festival held on 6-8 January 2017, where in the festival was introduced various tourism potentials owned Tista Village and socialize the Village Tista Stipulation as a rural tourism, so the whole Tista village community and the surrounding villages know that Tista Village is officially a rural tourism. For the community there must be a change of attitude in maintaining the status of the rural tourism, such as preserving the village environment, maintaining cleanliness, maintaining cultural and spiritual sustainability, growing creativity and innovation to cultivate and manage resources owned, and the most important is to increase knowledge and understanding related to tourism (hospitality). The tourist attraction of rural tourism certainly requires some concept of development and management that will be able to withstand longer tourist visits staying in Tista Rural Tourism. To provide a more diverse alternative tourism again, it is necessary to plan a package/local tourism products that can be packaged by the village community Tista a choice of attraction to tourists who visit. These local potentials that are part of life and daily activities of Tista Village community need to be introduced to tourists so that tourism development in Tista Rural Tourism can show something different, where potency which have chance to be developed is local culinary potency, where in Tista Village can be found in various local culinary communities that are very diverse from various preparations and flavors. In addition, to maintain a positive image of tourism in Tista Rural Tourism required something that is remembered and a characteristic that is obtained from the village Tista. Something that is a local souvenir, so that the Tista community need to be creative, both individually and in groups to prepare and produce local souvenirs whose nuance is the uniqueness and local wisdom of Tista. Because in tourism, what we "sell" is service accompanied by souvenir/hand brought by tourists to the area of origin and also as a promotional event to lure other tourists to come even more to the Tista Rural Tourism. For that reason, the Team of Community Service of the Faculty of Tourism, Udayana University implementing service in the Tista Rural Tourism with the topic "Packaging Local Culinary and Local Souvenirs in Support Tista Rural Tourism Development, Kerambitan District, Tabanan Regency".